2011
DOI: 10.1186/2047-783x-16-5-217
|View full text |Cite
|
Sign up to set email alerts
|

Surgical hip dislocation in symptomatic cam femoroacetabular impingement: what matters in early good results?

Abstract: In order to assess outcome and possible predictors of early good results, a prospective study on 22 patients who were treated with save surgical hip dislocation for symptomatic isolated cam-type femoroacetabular impingement (FAI) was performed. After a follow-up of 6 and 12 months, standard clinical and radiographic parameters were recorded. A statistically significant improvement of the clinical status according to the Harris hip score could be assessed at six months (p-value = 0.003) and 12 months (p-value =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…[ 96 ] 2016 IV Turkey Retrospective 48 n 21 HHS 1 33 OPEN Ishøi, L. [ 97 ] 2018 III Denmark Retrospective 33.1 y 189 HAGOS 1 51 ARTHROSCOPIC Ishøi, L. [ 98 ] 2019 III Denmark Retrospective 33.1 y 184 HAGOS 1 50 ARTHROSCOPIC Javed, A. [ 99 ] 2011 IV England Retrospective 30 n 40 mHHS, NAHS, satisfaction y/n 2 65 ARTHROSCOPIC Jochimsen, K. N. [ 100 ] 2019 III USA Retrospective X n 127 HOOS 1 26 ARTHROSCOPIC Jäger, M. [ 101 ...…”
Section: Resultsmentioning
confidence: 99%
“…[ 96 ] 2016 IV Turkey Retrospective 48 n 21 HHS 1 33 OPEN Ishøi, L. [ 97 ] 2018 III Denmark Retrospective 33.1 y 189 HAGOS 1 51 ARTHROSCOPIC Ishøi, L. [ 98 ] 2019 III Denmark Retrospective 33.1 y 184 HAGOS 1 50 ARTHROSCOPIC Javed, A. [ 99 ] 2011 IV England Retrospective 30 n 40 mHHS, NAHS, satisfaction y/n 2 65 ARTHROSCOPIC Jochimsen, K. N. [ 100 ] 2019 III USA Retrospective X n 127 HOOS 1 26 ARTHROSCOPIC Jäger, M. [ 101 ...…”
Section: Resultsmentioning
confidence: 99%
“…The included studies used a combination of imaging modalities: radiographs, magnetic resonance imaging (MRI), magnetic resonance arthrography (MRA), and computed tomography (CT) scans. In addition, seven studies (47 %) reported detailed information on radiographic criteria with defined parameters using degrees or ratios; however, many of the selected studies discussed criteria such as loss of offset, pistol grip deformity, centre‐edge angle, and alpha angle [1, 3, 6, 19, 20, 26, 39]. Finally, 2 of the 15 studies (13 %) described using diagnostic injections to confirm the diagnosis and indicate surgery [28, 29].…”
Section: Resultsmentioning
confidence: 99%
“…3 Previous studies have shown that cam deformity can extend to the anteromedial and posterior femoral head regions. 4,5 Osteoplasty at this particular region, otherwise known as the anteromedial "critical corner," can improve internal rotation of the flexed hip. However, this comes at a risk of causing iatrogenic damage to the primary vascular supply to the femoral head, the retinacular vessels from the ascending branch of the medial femoral circumflex artery.…”
mentioning
confidence: 99%
“…Due to the risk of vascular insult, it has been suggested that patients with posterior cam lesions should be treated with an open surgical dislocation rather than a hip arthroscopy. 5 This has proposed the advantages of direct visualization for a safe femoral osteoplasty to minimize femoral head osteonecrosis and fracture. Open surgical dislocation comes with a larger incision and potential complications from trochanteric nonunion, heterotopic ossification, neuropraxia, and residual abductor weakness.…”
mentioning
confidence: 99%